Labor migration and return: rural villages are places of refuge? (Revista LIDER, 2020)
Mexico has gone from a protected to a model of open and deregulated economy. The consequences of this passage for the field and agriculture are visible in rural employment, social conditions and mobility. This has changed the function of rural families. Based on the anthropological study of a rural village in Tlaxcala, Mexico, it has been observed that the families had developed a domestic economy that in the past sought the survival of the group, production and consumption of all, reciprocity and social responsibility and collective strategies, a set that turned into refuge for labor. Instead, rural families today are characterized more by forming multifunctional and diverse groups, where individual projects predominate.